Effect of High-Intensity Interval Training on Cardiovascular Risk Factor Parameters - M. R. Omar Siddiqi, Adnan Ghafoor, M. Hasan Siddiqui, M. Asim Rana, Salman Shakeel, Aroma Maqsood, Jahanzeb Kamal, Ali Nasir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: High-intensity interval training (HIIT) was thought to be effective on physiological parameters. Aim: To determine the effects of high-intensity interval training on lipid profile and other physiological parameters predominantly in men. Study design: Retrospective observational study Place and duration of study: United Medical & Dental College Karachi from 1st August 2021 to 31st January 2022. Methodology: One hundred and twenty six male subjects, either healthy or those with comorbid conditions like HTN and Type 2 DM, aged 20 to 70 years, and weighing ≥50 kg, were included. The subjects were required to complete pre and post-testing, which consisted of measures of body weight, blood glucose, lipid profile, serum glutamic pyruvic transferase (SGPT) and serum uric acid which were measured at baseline and 12 weeks after HIIT. Result: The mean age was 47.66±7.52 years. Body weight, blood glucose, SGPT and lipid profile significantly improved after HIIT training (p<0.05), while there was only a mean decline of 0.20±1.33 mg/dL (p=0.081) in the serum uric acid after HIIT. Conclusion: It was observed that 12 weeks with HIIT showed a significant change in blood glucose and lipid profile levels, indicating that HIIT might help reduce cardiovascular risk. Keywords: High-intensity interval training, Lipid profile, Glucose, Body weight, Cardiovascular risk factors